CONTEMPORARY DIRECTIONS OF TRANSFORMATIONS IN THE SETTLEMENT AND THE LANDSCAPE OF RURAL AREAS IN THE SILESIAN LOWLAND - Łach, Janusz; Szczepańska, Barbara (Quaestiones Geographicae, 2020)
Rural areas of the Silesian Lowland, undergoing social and economic transformations today, have had a strong impact on the formation of the region’s settlement landscapes. Political and economic changes after 1989 have affected the development of rural areas, in particular of ‘privileged’ settlements for which the proximity of towns and a trunk road are favourable factors. The result of these seemingly positive factors is the escape of young people (potential farmers) to the cities and an influx of new settlers. This affects social behaviour and activity, as well as the visual rural landscape, creating suburban zones with residential and leisure functions. The village seems to have lost its typical character but has it really? The subject of the research is, therefore, an analysis of changes in the spatial and social structure of a rural village as exemplified by Borek Strzeliński, which allows setting out its functions. The research issue is to determine the level of social activity of rural residents and their attitude towards the local cultural heritage, which influences their identity and the value of the landscape. The use of integrated methods of field work based on a free sociological survey has allowed identifying the spatial directions of village development and threats resulting from divided social activity.